Multiscale Metal Oxide Particles to Enhance Photocatalytic Antimicrobial Activity against Escherichia coli and M13 Bacteriophage under Dual Ultraviolet Irradiation - Su-Eon Jin; Hyo-Eon Jin (Pharmaceutics, 2021)
Antimicrobial activity of multiscale metal oxide (MO) particles against Escherichia coli (E. coli) and M13 bacteriophage (phage) was investigated under dual ultraviolet (UV) irradiation. Zinc oxide (ZnO), magnesium oxide (MgO), cuprous oxide (Cu2O), and cupric oxide (CuO) were selected as photocatalytic antimicrobials in MO particles. Physicochemical properties including morphology, particle size/particle size distribution, atomic composition, crystallinity, and porosity were evaluated. Under UV-A and UV-C irradiation with differential UV-C intensities, the antimicrobial activity of MO particles was monitored in E. coli and phage. MO particles had nano-, micro- and nano- to microscale sizes with irregular shapes, composed of atoms as ratios of chemical formulae and presented crystallinity as pure materials. They had wide-range specific surface area levels of 0.40–46.34 m2/g. MO particles themselves showed antibacterial activity against E. coli, which was the highest among the ZnO particles. However, no viral inactivation by MO particles occurred in phage. Under dual UV irradiation, multiscale ZnO and CuO particles had superior antimicrobial activities against E. coli and phage, as mixtures of nano- and microparticles for enhanced photocatalytic antimicrobials. The results showed that the dual UV-multiscale MO particle hybrids exhibit enhanced antibiotic potentials. It can also be applied as a next-generation antibiotic tool in industrial and clinical fields.